2013
DOI: 10.1016/j.micres.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Botrytis cinerea populations isolated from two open-field cultivated host plants

Abstract: The necrotrophic fungus Botrytis cinerea is reported to infect more than 220 host plants worldwide. In phylogenetical-taxonomical terms, the pathogen is considered a complex of two cryptic species, group I and group II. We sampled populations of B. cinerea on sympatric strawberry and raspberry cultivars in the North-East of Hungary for three years during flowering and the harvest period. Four hundred and ninety group II B. cinerea isolates were analyzed for the current study. Three different data sets were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…B83 yielded negative and faintly positive results in Flipper and Boty amplifications, respectively. All four transposon genotypes (vacuma, transposa, Flipper ‐only and Boty ‐only) have been found in B. cinerea populations of various origins at different frequencies (Isenegger et al ., ; Rajaguru & Shaw, ; Fekete et al ., ; Samuel et al ., ; Asadollahi et al ., ). As transposon genotyping is irrelevant for species discrimination (Walker et al ., ), this analysis did not provide additional information on the taxonomic status of isolate B83.…”
Section: Discussionmentioning
confidence: 97%
“…B83 yielded negative and faintly positive results in Flipper and Boty amplifications, respectively. All four transposon genotypes (vacuma, transposa, Flipper ‐only and Boty ‐only) have been found in B. cinerea populations of various origins at different frequencies (Isenegger et al ., ; Rajaguru & Shaw, ; Fekete et al ., ; Samuel et al ., ; Asadollahi et al ., ). As transposon genotyping is irrelevant for species discrimination (Walker et al ., ), this analysis did not provide additional information on the taxonomic status of isolate B83.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of B. cinerea isolates (86.7%) were virulent, whereas 13.3% of them, collected from different host plants, caused no infection on lettuce leaves. In fact, B. cinerea can infect a wide range of host plants and plant organs under laboratory conditions, and it had long been thought that B. cinerea had no host specificity [22] [23], while other studies had shown the occurrence of host specificity [52]. In addition, the Egyptian B. cinerea populations did not demonstrate any relation between TE genotype and isolate…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity of natural populations of B. cinerea causes them to exhibit extensive phenotypic variation and leads to great differences in reproductive patterns, pathogenicity and drug resistance [30][31][32]. During saprotrophic culture, fungi may also exhibit natural phenotypic variation due to various environmental factors [33].…”
Section: Discussionmentioning
confidence: 99%